Chapter Competenze e pratiche educative per realizzare la trasformazione verso economie e società sostenibili - MUGNAINI, SILVIA (Studies on Adult Learning and Education, 2022)
This work identifies the most significant studies addressing frameworks of 'competencies' aimed to be used to sustain a sustainability transformation, for both educators and learners, irrespective of the learning environment (formal, non-formal, informal) and the education level (primary, secondary, tertiary and adult education). To achieve this aim a critical review has been carried out. There is a prevalence of studies focusing on learners, on the formal learning environment, and on higher education. Additionally, a synthesis of existing frameworks of competencies is provided, for both learners and educators, which represents a launch pad for a new phase of empirical validation and testing.